Alternative Gavage Diet for Piscivores - Herman, Stephanie (Wildlife Rehabilitation Bulletin, 2016)
In 2010, PAWS Wildlife Center received a grant through the National Wildlife Rehabilitators Association (NWRA) to run a trial using an alternative gavage diet for piscivorous birds. Previous recipes primarily involved ground whole fish, which presents several problems including complicated preparation and an unreliable diet composition. PAWS’ new recipe, based on a fish–sourced canned pet diet, has shown to be a consistent, cost– and labor–effective alternative to ground fish diets. This paper discusses the unique dietary requirements of piscivorous birds, the composition and use of the new diet, and the data collected during the trial period.